OPTIMIZATION OF ENERGY SAVING SOLAR LAMP (LTSHE) WITH AUTOMATIC CONTROL FOR RURAL AREA IN INDONESIA - Rifqi Febrian, Muhammad
Indonesia as one of the largest archipelago countries in the world, still faced electricity due to geographical access. Solution which is given by the Government of Republic of Indonesia was launching a policy named preelectrification program. This policy aims is to increase the electrification ratio by providing energy saving solar lamp (called LTSHE in Indonesia) for the rural area in Indonesia. But the LTSHE still faced few problems related to it. The problems that arise are the LTSHE system specification didn’t meet the minimum standards that should be fulfilled. The other problem is the configration to reduce lamp power intensity is still done manually in the current LTSHE. Both of these problems lead to inefficiencies in the power system and poor performance of the system. Therefore the research was conducted to improve the system to be in accordance with the standards and also recommends a solution to reduce lamp power intensity automatically. Improving system specifications is done by mathematical calculations and also modeling and simulation in MATLAB software. The results of the simulation will be compared with the mathematical calculations performed. As for the method to automatically reduce lamp power intensity, we will use to two methods, there are PWM and current limiter. Later this two methods will be compared each other to determined which is more optimal to use in LTSHE. In this research in two methods, there will be mathematical calculations, then doing modeling and simulation on PSIM and Proteus. Then the two methods will be tested from the prototypes made. The LTSHE recommendation system is obtained by using PV which has Imp above 1.818A, lead acid 12V battery with a capacity above 28.67Ah, 12V lithium ion battery with a capacity above 1225mAh, and MPPT charge controller with P&O method and buck converter. While the method of setting the lamp power intensity will be better using the PWM method.